Application, limits, scoring and improvements of Groffman Visual Tracing test - Facchin, Alessio; Giordano, Lavinia; Brebbia, Giovanni; Maffioletti, Silvio (Scandinavian Journal of Optometry and Visual Science, 2020)
The Groffman Visual Tracing (GVT) test is a psychometric oculomotor test comprising two cards with five contorted and intersected lines, and which is available for the clinical evaluation of ocular movements. The participant starts from the letter at the top, follows the line, and reports the corresponding number at the bottom of each line. The aim of this study is to evaluate two claims made when details of the GVT test were originally reported: whether it is a developmental test, and the feasibility of its application starting from primary school children up to adults. This was achieved by using the GVT test and a simplified version of it. In two consecutive experiments, we tested two groups of children and adults. In the first experiment, 75 children (1st, 3rd, and 5th grade) and 25 adults underwent the GVT test. In the second experiment, 115 children from 1st to 5th grade underwent a simplified version of the test. Total scoring, accuracy and time to complete the test were evaluated. In the first experiment, 24% of children in the 1st and 3rd grades did not follow any lines correctly due to the difficulty of the test. In the second experiment, all participants were able to perform the test with both cards, and the accuracy improved significantly with age (p<0.0001). The time required to follow the lines was found to decrease with age (p<0.0001), and the accuracy improves (p<0.0001) compared with the standard version. The standard version of the GVT test has proven to be too difficult for younger children and a modified version produced improved results. Children at or below the 5th grade should to be tested using the modified version. Older children and adults can be tested with the standard version. Specific norms based on execution times and accuracy should to be established.